2019
DOI: 10.1089/tmj.2017.0319
|View full text |Cite
|
Sign up to set email alerts
|

Telepractice Treatment of Stuttering: A Systematic Review

Abstract: Live-stream, video telepractice appears to be a promising service- delivery method for treatment of stuttering using the Camperdown Program, Lidcombe Program, and integrated approaches. Further research is needed to determine if the initial evaluation and diagnosis of stuttering can be made using telepractice methodologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 20 publications
3
31
0
9
Order By: Relevance
“…A small amount of available data usually reports effectiveness and usefulness of telepractice in the adult population, mostly patients with post-stroke aphasia or Parkinson's disease (Hall, et al, 2013), communication and swallowing disorders (Molini-Avejonas, et al, 2015) or stuttering (McGill et al, 2019). Parsons et al (2017) reported a gain in parents' knowledge of treatment strategies which resulted in increased fidelity of indirect therapy delivered to their children with autism spectrum disorder (ASD).…”
Section: Application and Effectiveness Of Telepractice: Current Findingsmentioning
confidence: 99%
“…A small amount of available data usually reports effectiveness and usefulness of telepractice in the adult population, mostly patients with post-stroke aphasia or Parkinson's disease (Hall, et al, 2013), communication and swallowing disorders (Molini-Avejonas, et al, 2015) or stuttering (McGill et al, 2019). Parsons et al (2017) reported a gain in parents' knowledge of treatment strategies which resulted in increased fidelity of indirect therapy delivered to their children with autism spectrum disorder (ASD).…”
Section: Application and Effectiveness Of Telepractice: Current Findingsmentioning
confidence: 99%
“…autism spectrum disorder (ASD; Sutherland et al, 2018) and dysarthria (Hill et al, 2006). There is additional research to support telerehabilitation interventions for fluency disorders (McGill et al, 2018), dysphagia (Coyle, 2012), and voice disorders (Rangarathnam et al, 2016). For occupational therapy, telerehabilitation has long been touted as an emerging, promising area of practice that may alleviate problems such as patient access, cost of services, and allow practitioners to intervene within the natural environment (Cason, 2014;Eckberg Zylstra, 2013).…”
mentioning
confidence: 99%
“…Louis, 1997 ;St. Louis & Durrenberger, 1993 ), connecting a person who stutters to an SLP who specializes in stuttering may improve the treatment outcomes and/or provide more individualized treatment options (McGill et al, 2019).…”
Section: Telepracticementioning
confidence: 99%
“…A recent systematic review by McGill et al (2019) of seven studies including 80 participants who stutter highlighted that speech therapy services using telepractice using a variety of formats (i.e., purely telepractice or a hybrid, in-person and telepractice) as well as populations (i.e., children, adolescents and adults) appeared to produce positive outcomes for the treatment of stuttering and showed promise for future research.…”
Section: Stuttering and Telepracticementioning
confidence: 99%